THE CONCEPT OF A QUANTUM AND ITS PHYSICAL MEANING - Kholikov Kamoliddin Abdig’aniyevich (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the development of views on the study of the concept of "quantum".Quantum theory describes three of the four fundamental types of interactions –electromagnetic, strong and weak. And currently, the active study of this field of physics continues. However, this work was based on the study of the history of the discovery of the concept of "quantum" and its physical meaning.